Mathematics teaching expertise: A study of the dimensionality of content knowledge, pedagogical content knowledge, and content-specific noticing skills - Copur-Gencturk, Yasemin; Tolar, Tammy (Teaching and teacher education, 2022)
Identifying the nature of the expertise needed to teach a subject matter is instrumental in preparing the teaching workforce. Scholars have stressed the subject-specific nature of such expertise and theorized that to teach a given subject matter, teachers need distinct manifestations of content-specific knowledge and skills. Yet empirical studies supporting the distinguishability of these constructs have been mixed. This study aims to add to the field by showing how different conceptualizations of teachers' content knowledge may have affected the dimensionality of these constructs in prior studies. It also builds further understanding of whether content specific noticing is a separate construct from content and pedagogical content knowledge for elementary school mathematics teachers. Data was collected from 290 teachers from 48 states in the United States and our findings indicate that teachers' content-specific expertise for teaching mathematics is multidimensional. The findings suggest that content knowledge (with two distinct components), pedagogical content knowledge, and content-specific noticing skills are separate components of teachers’ expertise for teaching mathematics. Furthermore, our findings underscore the influence that the conceptualization of content knowledge has on the empirical results for the dimensionality of the construct. •Prior research on the dimensionality of math knowledge for teaching has shown mixed outcomes for elementary school teachers.•How content knowledge is conceptualized affects the dimensionality of mathematical knowledge for teaching.•Content-specific noticing, pedagogical content knowledge, mathreasoning, and active math knowledge are distinct components of mathteaching expertise.